THE ECONOMIC IMPACT OF E-COMMERCE ON MSMES: OPPORTUNITIES AND CHALLENGES IN THE DIGITAL ERA - Nizar Alpian Pratama; M. Yusron Zahidi; Taufik Chaidir (Laboratorium Riset Ekonomi, 2024)
The development of e-commerce has provided significant opportunities for MSMEs, especially in expanding markets and reducing operational costs. However, the use of e-commerce among MSME players is still low due to barriers such as lack of digital infrastructure and technological literacy. This study examines the economic impact of e-commerce on MSME players, as well as the opportunities and challenges they face. While e-commerce has great potential, many MSMEs still struggle to optimize it. Therefore, the role of government and stakeholders in improving digital literacy and infrastructure is crucial to advancing MSMEs in the digital era.